2023
DOI: 10.1001/jamanetworkopen.2023.28934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cannabis Use Disorder and Reasons for Use Among Adults in a US State Where Recreational Cannabis Use Is Legal

Gwen T. Lapham,
Theresa E. Matson,
Jennifer F. Bobb
et al.

Abstract: ImportanceMedical and nonmedical cannabis use and cannabis use disorders (CUD) have increased with increasing cannabis legalization. However, the prevalence of CUD among primary care patients who use cannabis for medical or nonmedical reasons is unknown for patients in states with legal recreational use.ObjectiveTo estimate the prevalence and severity of CUD among patients who report medical use only, nonmedical use only, and both reasons for cannabis use in a state with legal recreational use.Design, Setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Our study found that among the 74.8% of patients who completed cannabis screening, nearly 1 in 5 adult primary care patients reported recent cannabis use, among whom a third were at moderate to high risk for CUD. These rates are higher than those among adults in the general population; however, our results are comparable with the small number of recent studies that have estimated cannabis use within health care settings . We also found that while a minority of patients reported using cannabis for strictly medical reasons, most of those who reported cannabis use reported using it to manage a specific health symptom.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study found that among the 74.8% of patients who completed cannabis screening, nearly 1 in 5 adult primary care patients reported recent cannabis use, among whom a third were at moderate to high risk for CUD. These rates are higher than those among adults in the general population; however, our results are comparable with the small number of recent studies that have estimated cannabis use within health care settings . We also found that while a minority of patients reported using cannabis for strictly medical reasons, most of those who reported cannabis use reported using it to manage a specific health symptom.…”
Section: Discussionsupporting
confidence: 83%
“…These rates are higher than those among adults in the general population; however, our results are comparable with the small number of recent studies that have estimated cannabis use within health care settings. 1 , 16 , 31 , 32 We also found that while a minority of patients reported using cannabis for strictly medical reasons, most of those who reported cannabis use reported using it to manage a specific health symptom. This aligns with another study 29 that found that this type of cannabis use is clinically underrecognized, and without specifically screening for medical cannabis use, clinicians may not ask and patients often do not disclose their use.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Cannabis use disorders are the primary contributor that cannabis use makes to the global burden of disease 11 and could increase the risk of further adverse cannabis outcomes because characteristic symptoms involve using more cannabis than intended, and difficulty controlling or cutting down use. 9 Given that cannabis use disorders are prevalent in people who use cannabis for medical as well as non-medical purposes, 12 preventing and treating CUDs should be a key focus in clinical practice and policies designed to maximise benefits and minimise risks.…”
Section: Articlementioning
confidence: 99%